De Medellín à Aparecida: a opção preferencial pelos pobres e a missão da Igreja - Dias, Claudinei (2021)
This work has as objective the understanding of the Mission of the Church in accordance with the General Conferences of the Episcopate of Latin-American and Caribbean - CELAM, in the evangelical preferential option for the poor. The aim is to analyze in the texts of the Conferences what the Church has actually accomplished about the challenging proposal of evangelization to fight poverty and protect the poor according to theology and in the conclusions of the documents of the Conferences, responding to the concern of the Latin-American Church in relation to its reality and within its context of society with its pluralities and diverse cultures, which need a closer look at the life of its people with its difficulties and anguishes. The method "See-JudgeAct", an epistemological instrument used by the Magisterium and present at the Conferences, offers tools for notes, reflections, analysis and conclusions on the social problems of the continent and that require urgent transformation of reality, resulting in a theological-pastoral reflection less dependent on the European and basing the decisions to be applied in a certain pastoral action of the Church identified with the native people. To this end, at each Conference the Latin American and Caribbean Church, based on the documents of the Vatican Council II and the Magisterium, prophetically denounces and announces the needs of its people, supported by the light of the Gospel and showing that men and women, throughout their histories and time, are protagonists of their existence, where the Church, people of God, make themselves present in this Latin-American continent